2013
DOI: 10.1063/1.4811385
|View full text |Cite
|
Sign up to set email alerts
|

Shock-less interactions of ablation streams in tungsten wire array z-pinches

Abstract: Shock-less dynamics were observed during the ablation phase in tungsten wire array experiments carried out on the 1.4 MA, 240 ns MAGPIE generator at Imperial College London. This behaviour contrasts with the shock structures which were seen to dominate in previous experiments on aluminium arrays [Swadling et al., Phys. Plasmas 20, 022705 (2013)]. In this paper, we present experimental results and make comparisons both with calculations of the expected mean free paths for collisions between the ablation streams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…Related studies include counter-streaming laser-produced plasmas supporting hohlraum design for indirect-drive inertial confinement fusion [17][18][19] and for studying astrophysically relevant shocks, [20][21][22][23][24] colliding plasmas using wire-array Z pinches, 25,26 and applications such as pulsed laser deposition 27 and laser-induced breakdown spectroscopy. 28 Primary issues of interest in these studies include the identification of shock formation, the formation of a stagnation layer [29][30][31] between colliding plasmas, and the possible role of two-fluid and kinetic effects on plasma interpenetration.…”
Section: Introductionmentioning
confidence: 99%
“…Related studies include counter-streaming laser-produced plasmas supporting hohlraum design for indirect-drive inertial confinement fusion [17][18][19] and for studying astrophysically relevant shocks, [20][21][22][23][24] colliding plasmas using wire-array Z pinches, 25,26 and applications such as pulsed laser deposition 27 and laser-induced breakdown spectroscopy. 28 Primary issues of interest in these studies include the identification of shock formation, the formation of a stagnation layer [29][30][31] between colliding plasmas, and the possible role of two-fluid and kinetic effects on plasma interpenetration.…”
Section: Introductionmentioning
confidence: 99%
“…These flows are produced using the Magpie 5 pulsed power generator at Imperial College (1.4 MA, 240 ns); the flows are accelerated by the J × B forces that arise due to the interaction of the current conducted by the plasma with the associated selfmagnetic field. Careful design of the load allows the geometry of the flows to be controlled and focused in order to produce quasi-1D flows, 6,7 cylindrically symmetric interactions, 8 or jet into ambient medium interactions. 9,10 The collisional scale lengths of the interactions can be tuned both through the choice of the element used to produce the plasmas (typically tungsten or aluminium) and through control of the timing of measurements, allowing the study of both shock formation and long-range flow interpenetration.…”
Section: Introductionmentioning
confidence: 99%
“…A series of experiments were carried out in order to investigate ablation stream interaction dynamics using an interferometric imaging diagnostic; 2,3,7,14 in these experiments, a probe laser was aligned along the axis of the array in order to measure the axially integrated, radially and azimuthally resolved ("end-on") free electron density distribution ( Ð n e dz) of the plasma. Aluminum and tungsten wire arrays were investigated; previous calculations [15][16][17] had indicated that while the ablation streams produced by aluminum arrays should mostly interact collisionally, those produced by tungsten arrays should remain collisionless for a significant portion of the experiment.…”
Section: Interferometric Evidence Of Changes In Collisional Dynamicsmentioning
confidence: 99%
“…[2][3][4][5] These experiments were conducted on the 1.4 MA, 240 ns Magpie pulsed power driver at Imperial College London, 6 and diagnosed using a range of techniques, including laser interferometric imaging, optical Thomson scattering (TS), and Faraday rotation imaging. 7 The range of quantitative measurements resulting from this work is highly suitable as a source for the benchmarking of computer codes designed to model complex plasma physics problems involving flow interpenetration, magnetic field advection, and the atomic physics of high Z, multi-fluid plasmas.…”
Section: Introductionmentioning
confidence: 99%